(untitled) (Forum Penelitian Agro Ekonomi, 2024)
The main objective of this paper is to show that the concept of food security should not be separated from hunger given that measures, such as of food sufficiency per capita or household food purchasing power, cannot by themselves indicate the quality of human resources in one country. There exists an X-factor between food sufficiency per capita on the one hand, and human resources quality on the other hand, that must be analysed. In 2017, the Global Hunger Index (GHI) values of 14 achieved by developing countries managed to match those of developed countries. This opens the opportunity, particularly for Indonesia, to re-examine non-income variables and establish policy frameworks to solve hunger. A key component to the issue is the persistent lack of animal protein consumption in Indonesia and elsewhere. This paper suggests that animal protein must be produced in a way that economically cheap and frees the production system from environmental deterioration and problems arising from antibiotic resistance.